IN VITRO α-AMYLASE AND Α-GLUCOSIDASE INHIBITOR ACTIVITIES OF ALBIZIA PROCERA STEM BARK - D, Anand; M, Sathish; Ls, Dhivya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This current study was carried out to determine the in vitro α-amylase and α-glucosidase inhibitory activity of extract and fractions of Albizia procera. Methods: The α-amylase and α-glucosidase inhibition assay was carried out at concentrations 50–2000 μg/ml and acarbose used as standard. The absorbance was measured at 540 nm and recorded by spectrophotometer. Percentage inhibition was calculated for both the assays. Preliminary phytochemical screening was also evaluated using standard procedures. Results: There was a dose-dependent percentage inhibition of extracts (petroleum ether and ethanol) and fractions (chloroform, ethyl acetate, and n-butanol). The ethanol extract and n-butanol fraction show good inhibitory activity against both α-amylase and α-glucosidase with the percentage inhibition of 86.20% and 88.20% and 83.13% and 87.10%, respectively. The preliminary phytochemical screening shows that ethanol extract consists of active constituents such as flavonoids and phenolic compounds and tannins. Conclusion: This finding suggests that the ethanol extract and n-butanol fraction show good inhibitory activity against both α-amylase and α-glucosidase and show good antidiabetic activity.